2014
DOI: 10.1177/0004867414531459
|View full text |Cite
|
Sign up to set email alerts
|

Understanding service demand for mental health among Australians aged 16 to 64 years according to their possible need for treatment

Abstract: Background:To inform decisions about mental health resource allocation, planners

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…The results also compare well with other initiatives that involve the large-scale implementation of psychological treatments (41,46), and the high level of patient satisfaction indicates the acceptability of online treatment. The amount of therapist time spent during treatment indicates that the service is likely to be cost-effective in comparison with traditional services (25) and thus is currently the subject of a health economics evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also compare well with other initiatives that involve the large-scale implementation of psychological treatments (41,46), and the high level of patient satisfaction indicates the acceptability of online treatment. The amount of therapist time spent during treatment indicates that the service is likely to be cost-effective in comparison with traditional services (25) and thus is currently the subject of a health economics evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were required to complete an assessment before beginning treatment and were ineligible for online treatment if they were acutely suicidal, were engaged in regular psychotherapy, or had clinical presentations deemed to require comprehensive face-to-face assessment. People with subclinical symptoms were eligible for treatment at the clinic (24)(25)(26), as were those taking psychotropic medication.…”
Section: Patientsmentioning
confidence: 99%
“…There has been recent criticism of binary classification systems such as the DSM, which take the assumption that people should be classified as either having or not having a particular psychopathological disorder (Hankin et al, 2005), with suggestions that depression may occur on a continuum (Solomon et al, 2001), particularly so in youth (Hankin et al, 2005). In light of this, other outcomes in depression treatment that take into account the disability Survey of Mental Health and Wellbeing found that a significant proportion of those who had used mental health services in the past 12 months did not have a formally diagnosed mental disorder, but had other indicators of possible need, including maintenance treatment following a previous episode or significant psychological distress in the absence of a diagnosis (Harris et al, 2014). Thus, in addition to using classification systems such as ICD and DSM to determine mental disorder diagnoses and symptom screening scales to measure symptom severity, researchers examining the efficacy of depression prevention and treatment interventions should also consider including items assessing functional impairment, as this may be a useful indicator of disability and need for treatment, even if a formal mental diagnosis is not given (Üstün and Kennedy, 2009).…”
Section: Limitationsmentioning
confidence: 99%
“…Many people experiencing increasing symptoms and psychological distress do not meet the criteria for a hospital admission, but do require additional support (Harris et al . ). Sub‐acute residential services are increasingly being implemented in Australia to support people in their recovery, through promoting independence and illness self‐management.…”
Section: Introductionmentioning
confidence: 97%